Response of Different Doses of Nitrogen on Broccoli (Brassica oleracea var. italica) in Lamjung District - Bika, Ravi; Bhandari, Nirajan; Khanal, Amit (International Journal of Applied Sciences and Biotechnology, 2018)
The study was carried out to examine the optimum dose of Nitrogen on Broccoli in Institute of Agriculture and Animal Science, Lamjung Campus during Sept, 2015- Jan, 2016. Six treatment Viz. 50, 100,150,200, 250, 300 kg/ha of Nitrogen with same level of P and k (160:100 kg/ha) and FYM (20 t/ha) were used in a Randomized Complete Block Design with three replications. Effect of treatments on plant height, leaf area and head weight plant-1, yield ha-1 were significant and other parameters (leaf number, SPAD reading, plant spreading) were not affected by the treatments. Treatment that received 300 kg N ha-1 gave the maximum yield ha-1 (14.77 ton) which was followed by treatment that received 250 kg N ha-1 (10.60 ton), 200 kg N ha-1 (8.11 ton), 150 kg N ha-1 (7.432 ton), 100 kg N ha-1 (5.96 ton) and 50 kg ha-1 (4.24 ton). Treatments 250 kg N ha-1, 200 kg N ha-1, 150 kg N ha-1 and 100 kg N ha-1 were statistically at par while 50 kg produced the least yield ha-1. Application of 300 kg N ha-1 gave the higher result with respect to plant height (17.75 cm), leaf area (699.32 cm2), leaf number (7.77), SPAD reading (68.71), plant spreading (70.21 cm), compared to other treatments while minimum result obtained from application of 50 kg N ha-1. Hence, we can conclude that the total head production increased with increased N Int. J. Appl. Sci. Biotechnol. Vol 6(3): 270-273